Efficacy and Safety of Tacrolimus Therapy for a Single Chinese Cohort With Very-Late-Onset Myasthenia Gravis - Zheng, Yiming; Yuan, Xiaoqiu; Zhang, Caifeng; Liu, Ran; Jin, Haiqiang; Hao, Hongjun; Li, Fan; Zhao, Yawen; Yuan, Yun; Wang, Zhaoxia; Gao, Feng (Frontiers in Neurology, 2022)
Background and Purpose: Previous studies have found tacrolimus to be a favorable drug for treating different types of myasthenia gravis (MG), but few have focused on very-late-onset MG (VLOMG). This study evaluated the efficacy and safety of tacrolimus for VLOMG therapy. Methods: This was a retrospective single-center cohort study of 70 patients with VLOMG (onset≥65 years) who visited Peking University First Hospital in 2019. Participants were divided into the tacrolimus (Tac) group and the control group based on tacrolimus usage. We further divided the Tac group into patients treated without corticosteroids and with corticosteroids. Sociodemographic features, clinical profiles, and outcomes were compared between different therapies and further analyzed by multivariate regression. Details of tacrolimus treatment, comorbidities, and adverse drug reactions (ADRs) were described. Results: Among 70 patients, the median (interquartile range) age at onset was 71 (68-77) years, and the follow-up duration was 27 (27-29) months. Most patients were type I (28%) and III (40%) according to the Myasthenia Gravis Foundation of America (MGFA) classification. In the Tac group, tacrolimus treatment was maintained for 36 (27-52) months. The dosage at the final evaluation was 1.0 (1.0-1.75) mg/day, and the last blood concentration test was 4.25 (2.85-5.7) ng/ml. Forty-three percent reached remission, and 37% improved based on MGFA post-intervention status (MGFA-PIS). For the 9 patients newly diagnosed at enrollment within this group, MG activities of daily living (MG-ADL) decreased significantly from 3 (2-5) to 2 (1-2) (p=0.041). Regarding the 13 patients coadministering Wuzhi capsules, the tacrolimus concentration increased from 2.75 (1.4-3.8) ng/ml to 5.95 (5.1-7.0) ng/ml (p=0.012). No significant differences in outcomes were observed between tacrolimus treatment without and with corticosteroids or between the Tac group and the control group. Ninety-three percent had at least one comorbidity. ADRs related to tacrolimus emerged in 25% (9/36) of patients, most of which were not serious and reversible. Conclusions: Tacrolimus is effective and safe in treating VLOMG. Tacrolimus monotherapy without corticosteroids can be used as an initial and maintenance treatment for VLOMG. Wuzhi capsules work well in elevating tacrolimus concentrations in this population.